SINERGISITAS GURU PAI DAN ORANG TUA DALAM PENANAMAN MORAL PESERTA DIDIK DI SMP ASY-SYIFA DARUSSALAM ABUNG JAYO LAMPUNG UTARA - Selvia, Devi Sela Eka (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2024)
ABSTRACTAll humans certainly need education for their survival, because all aspects of life will require insight gained from education. The existence of education can guarantee the development and survival of the Indonesian nation. Therefore, the commitment and responsibility of those responsible for education must be increased. And it is no less important that a person's position can determine the success of the educational institution he leads, especially in relation to the role of the school principal and the teacher council and parents in ensuring the smooth running of the teaching and learning process.This research aims to: 1) Find out the synergy of PAI teachers and parents in cultivating students' morals at Asy-Syifa Darussalam Abung Jayo Middle School, North Lampung; 2) Knowing the supporting and inhibiting factors for the synergy of Islamic Religious Education Teachers and parents in cultivating students' morals at Asy-Syifa Darussalam Abung Jayo Middle School, North Lampung. This type of research is descriptive qualitative where the results of data obtained in the field are explained in the form of sentence descriptions, with the research object being Islamic Religious Education teachers and parents, as well as students at Asy-Syifa Darussalam Abung Jayo Middle School, North Lampung. In collecting data, three methods were used, namely interviews and observation as the main method, then documentation as a supporting method to complete the data that the researcher did not obtain through interviews and observation.The results of this research show that; 1) The synergy of teachers and parents in instilling moral discipline and politeness in students at Asy-Syifa Darussalam Abung Jayo Middle School, namely through Tahfidz activities and discipline sheets. In the discipline sheet there are two discipline values, the first is discipline at home and discipline at school; 2) Factors that influence the synergy of PAI teachers and parents in instilling the morals of students at Asy-Syifa Darussalam Abung Jayo Middle School, North Lampung. There are two influencing factors, namely: a) Supporting factors for the synergy of PAI teachers and parents in instilling the morals of participants. students at Asy-Syifa Darussalam Abung Jayo Middle School, North Lampung, namely Consistency in Education, Attitude of parents in the family, Understanding and practicing the religion they adhere to, Consistent attitude of parents in implementing norms. family factor, if the family factor understands religion and educates their children well and instills good moral values then it will be easy for teachers to instill good morals and as parents the same goes for parents; b) The inhibiting factor is from the parents themselves, by educating them by giving a good example, the child will easily be instilled with good morals, the second is the environment, if the environment is good then the child will more easily be instilled with good values, habits, such as if he makes a mistake in advise but just stay silent and sulk.. Keywords:   Synergy, Moral Cultivation